History, situation and reinforcement of the bell towers of the basilica of Penha-Recife-Brazil - Sobrinho, C. W. A. P.; Costa, A. C. (Revista ALCONPAT, 2016)
This paper presents and discusses the history, current situation, original techniques and strategies used in the development of structural reinforcement design of both towers of the Basilica of Penha Church. Repair techniques poorly designed, conducted in 1981, along with lack of preventive maintenance, leaks and even the growth of bushes embedded in the masonry led to the instability of the towers of the Basilica of Penha Church.Keywords: reinforcing masonry; historic monuments; reinforcement techniques; execution strategies; carbon fibers.